The influence of novel bromine sequestration agents on zinc/bromine flow battery performance. Issue 112 (21st November 2016) - Schneider, Martin; Rajarathnam, Gobinath P.; Easton, Max E.; Masters, Anthony F.; Maschmeyer, Thomas; Vassallo, Anthony M.
Abstract : This study benchmarks cycle performance of electrolyte solutions containing novel bromine sequestration agents (BSA) in a zinc bromine flow battery. Abstract : This study benchmarks cycle performance of electrolyte solutions containing novel bromine sequestration agents (BSA) in a zinc bromine flow battery. Five alternative BSA candidates – 1-ethyl-1-methylpiperidinium bromide ([C2 MPip]Br), 1-ethylpyridinium bromide ([C2 Py]Br), 1-(2-hydroxyethyl)-pyridinium bromide ([C2 OHPy]Br), 1-ethyl-3-methylimidazolium bromide ([C2 MIm]Br) and 1-(2-hydroxyethyl)-3-methylimidazolium bromide ([C2 OHMIm]Br) were investigated under operational conditions typical for zinc bromine flow batteries. Results were compared to the conventional BSA, 1-ethyl-1-methylpyrrolidinium bromide ([C2 MPyrr]Br). Electrolytes containing the various alternative BSAs were tested at bench scale in a full-cell battery setup under controlled electrolyte flow and temperature. The evaluated performance parameters were: voltaic efficiency, coulombic efficiency, energy efficiency and recoverable charge. A correlation between BSA–bromine bond strength and cycle performance was observed. Performance of the tested electrolytes varied widely, and gains in coulombic efficiency were generally offset by losses in voltaic efficiency. [C2 Py]Br and [C2 MIm]Br produced cycle performance improvements compared to the other BSAs studied.